ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN STUNTING PADA BALITA DI WILAYAH PUSKESMAS KABUPATEN PATI - Sulistiyaningsih, Sri Hadi; Niamah, Siti (Coping: Community of Publishing in Nursing; Vol 8 No 4 (2020): Desember 2020, 2020)
Stunting is a condition of failure to thrive in children under five years of age as a result of chronic malnutrition so that the child is too short for his age. Malnutrition occurs since the baby is in the womb and the early days after the baby is born, however, the condition of stunting only appears after the baby is 2 years old. The purpose of this study was to analyze the factors that influence the incidence of stunting in children under five in the Pati District Health Center. This research is explanatory research with a cross-sectional approach. The sample of this study was 59 children under five who experienced stunting, which was taken using the total sampling technique. The analysis used is the Chi-Square test and multiple logistic regression analysis. The results showed a relationship between Knowledge (p-value = 0.039), Birth Weight (p-value = 0.020), Economic Factors (p-value = 0.001), and Parenting Patterns (p-value = 0.021), History of Breastfeeding (p-value = 0.040). ) and a history of infectious disease (p-value = 0.014) with the incidence of stunting. The variables that influence stunting together are birth weight (p-value = 0.007), economic factors (p-value = 0.011), and parenting style (p-value = 0.004). Based on the results of the study, it is suggested that the community, especially mothers and families with children under 5 years of age, comply with and implement programs related to the provision of balanced nutrition for toddlers and increase creativity in feeding their children.